2009
DOI: 10.1007/s10646-009-0370-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of exposure to metal contamination and lipid peroxidation in the benthic fish Cathorops spixii from two estuaries in South America, Brazil

Abstract: Biomarkers as lipid peroxidation, metallothionein and delta-aminolevulinic acid dehydratase were determined in Cathorops spixii to compare the biological responses of this fish from estuaries with distinct anthropogenic influence. Three areas were selected in two estuaries in accordance with the levels of contamination for the polluted (Santos/São Vicente) and with the hydrodynamic characteristics for the non-polluted (Cananéia) estuary. Water characteristics and mercury levels in C. spixii confirmed a high hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 26 publications
0
30
3
4
Order By: Relevance
“…However, some studies have indicated the presence of toxic metals, including Pb, Cd, Cu, Zn and Hg in this region in recent years (AZEVEDO et al, 2011;AZEVEDO et al, 2012a;AZEVEDO et al, 2012b). The presence of Hg in this estuary is partly to be explained by the presence of an abandoned gold mine and the fertilizer factory located in Iguape, in the northern portion of the estuary.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, some studies have indicated the presence of toxic metals, including Pb, Cd, Cu, Zn and Hg in this region in recent years (AZEVEDO et al, 2011;AZEVEDO et al, 2012a;AZEVEDO et al, 2012b). The presence of Hg in this estuary is partly to be explained by the presence of an abandoned gold mine and the fertilizer factory located in Iguape, in the northern portion of the estuary.…”
Section: Introductionmentioning
confidence: 94%
“…This estuary also contains the largest commercial harbor in South America and, with approximately 1100 industries (such as fertilizers and pharmaceuticals), it is one of the most important petrochemical and metallurgical industrial areas in Brazil. Some authors have reported high concentrations of different chemical pollutants, for instance metals such as Pb, Cd, Zn and Cu introduced into this coastal aquatic system as a result of the various industrial activities undertaken in the inner area of the estuary (BOLDRINI; NAVAS-PEREIRA, 1987;AZEVEDO et al, 2011;AZEVEDO et al, 2012a). The rapid increase in urbanization and industrialization, mainly in the last 50 years, has led to the degradation of the coastal mangrove habitat through contamination with effluents from industrial and domestic sources and solid waste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, inhibition of GST was observed in Pseudorasbora parva exposed to methomyl (carbamate) (Li et al 2008). It also should be considered that the activities of GST and LPO vary widely between fish species (Solé et al 2006, Sanchez et al 2007, Azevedo et al 2009. Nevertheless, characterization of these non-specific biomarkers is necessary if the species is going to be used in field monitoring, considering that in the environment, organisms would be exposed to unknown mixtures of pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, most of the studies concerning species-specific ecotoxicology, and its use to establish limits and regulations have been carried out in North America and Europe (US-EPA 1986, OECD 2007. Some studies has been carried out in South America and Mexico (Akaishi et al 2002, de la Torre et al 2005, Azevedo et al 2009, González-Mille et al 2010), but information is scarce for Central America.…”
mentioning
confidence: 99%